KONTRIBUSI IBU RUMAH TANGGA TERHADAP PENDAPATAN KELUARGA DI DESA KINILOW KECAMATAN TOMOHON UTARA - Ribka M Kumaat (Sam Ratulangi University, 2011)
This research aims to study the contribution of housewives bamboo craftsman anya-man against the Village Kinilow family income in North Tomohon District. The benefits of this research that can be used as information material for students who want to know more about the activities of the housewife in supporting family income and consideration for future research. The results showed that the contribution of IRT when viewed on the basis of the husband's occupation IRT greatest contribution was the kind of husband's job as a motorcycle that is equal to 46.29 percent. Also the results showed that the contribution of IRT to the family income by an average of 36.05 per cent, 46.22 per cent while the contribution of the husband, and the contribution of children to family income is equal to 17.73 percent.